2022
DOI: 10.1038/s41588-022-01032-z
|View full text |Cite
|
Sign up to set email alerts
|

HLA autoimmune risk alleles restrict the hypervariable region of T cell receptors

Abstract: Polymorphisms in the human leukocyte antigen (HLA) genes strongly influence autoimmune disease risk. HLA risk alleles may influence thymic selection to increase the frequency of T cell receptors (TCRs) reactive to autoantigens (central hypothesis). However, research in human autoimmunity has provided little evidence supporting the central hypothesis. Here we investigated the influence of HLA alleles on TCR composition at the highly diverse complementarity determining region 3 (CDR3), which confers antigen reco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 51 publications
3
29
0
Order By: Relevance
“…Our group recently showed that the amino acid frequencies at complementarity-determining region 3 (CDR3) of the T cell receptor (TCR) are highly influenced by the HLA alleles and amino acids, possibly through thymic selection 6 . This type of analysis is an extension of the analyses we described in the previous sections.…”
Section: Multi-trait Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Our group recently showed that the amino acid frequencies at complementarity-determining region 3 (CDR3) of the T cell receptor (TCR) are highly influenced by the HLA alleles and amino acids, possibly through thymic selection 6 . This type of analysis is an extension of the analyses we described in the previous sections.…”
Section: Multi-trait Analysismentioning
confidence: 99%
“…As spurious associations again arise when the frequencies of the tested alleles are relatively low 6 , we recommend performing permutation analyses to confirm the calibration of the test statistics.…”
Section: Multi-trait Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…DQ8 has a primary role in disease initiation through presentation of peptide epitopes to the autoreactive CD4 + T-cell receptors (TCR) from the N-terminal region of the insulin B chain, including residues 9-23 and 9-25 (B:9-23; B:9-25; Methods) [1][2][3][4][5][6][7] . It is already established that TCR repertoire differences from the thymus, mediated in part through variable a and b complementarity-determining region (CDR3) 3 regions and their interactions with peptide epitopes and amino acids in the peptidebinding cleft of HLA class II molecules, are determined by HLA class II genotype [21][22][23][24][25][26][27] .…”
Section: Mainmentioning
confidence: 99%